Applying the Consensus Reporting Items for Studies in Primary Care Checklist to Improve Reporting Quality in Primary Care Research in China - YANG Hui, WANG Yang, CHEN Qingqi, LIU Chenxi, GU Jie, ZHAO Yang, QIN Jiangmei, CAO Xinyang, Sturgiss Elizabeth, Phillips William R., XU Yanli (Zhongguo quanke yixue)
In 2023, the Consensus Reporting Items for Studies in Primary Care (CRISP) Working Group introduced a consensus checklist aimed at enhancing the quality, practicality, and dissemination of research reports in general practice and primary care. The editorial team of the Chinese General Practice Journal translated the CRISP checklist into Chinese and conducted a review of the current status of primary care research in China. The review identifies major problems in the field, including six common problems: "author-centered orientation" "overemphasis on authority" "uncritically adopting international experience" "lack of rigor in reporting methodologies" "inclusion of excessive and redundant information" and "lack of transparency". Finally, the editorial team encourages authors, editors, and reviewers in China to adopt the CRISP checklist to improve the quality of primary care research reports. Additionally, the review provides specific recommendations for applying the CRISP Checklist in various subfields, such as discipline development research, clinical research, health services research, health policy research, medical education research, and community epidemiological research.